COMPARATIVE EFFECT OF ANKLE PUMPING EXERCISE AND BRISK WALKING ON DIABETIC PATIENTS WITH PERIPHERAL NEUROPATHY (Journal of Medical & Health Sciences Review, 2025)
Background: Diabetes mellitus (DM), sometimes known as just diabetes, is hyperglycemia, a physiologically abnormal condition characterized by consistently elevated blood glucose levels. Diabetic neuropathy (DN) is largely predicted by two factors: the severity of diabetes and hemoglobin A1c levels. The latter is associated with metabolic factors, inherited risk factors, environmental factors, common cardiovascular risk factors, and poor glycemic management. Ankle pumping exercises, which involve flexing and extending the ankle joint, are beneficial for people with diabetic neuropathy. Brisk walking has various benefits for those with diabetic neuropathy, such as better circulation, less pain, and enhanced balance. Aims and Objectives: This is a Randomized clinical trial study, the main objective of this study to compare the effects of brisk walking and ankle pumping exercises in patients with diabetic neuropathy.  Material and Methods: 46 participants were enrolled by using non-probability purposive sampling technique within the three- to four-month trial. Patients between the ages of 35 and 55 who had diagnosed with diabetes with peripheral neuropathy were recruited via purposive sampling. Participants who had 2nd grade foot ulcer, had any CVS pathology, had any advanced complication such as diabetic retinopathy were excluded from study. Validated instruments such as Michigan neuropathy screening inventory, diabetic quality of life, & NPRS scale were used to gather data. Data Analysis: Data was analyzed on SPSS-25. Result: The result of this study proved that using brisk walking can be the possible way to reduce peripheral neuropathy. Conclusion: The recent study showed that the brisk walking and ankle pumping exercises prove to be the best for improving peripheral neuropathic symptoms among diabetic patients. But the brisk walking proved to be the better than ankle pumping exercises.